The effect of towing a range of relative resistances on sprint performance - Murray, A.; Aitchinson, T. C.; Ross, G.; Sutherland, K.; Watt, I.; McLean, D.; Grant, S. (Journal of Sports Sciences, 2005)
The aim of this study was to compare sprint performance over 10 and 20m when participants ran while towing resistances, weighing between 0 and 30% of body mass. The sample of 33 participants consisted of male rugby and soccer players (age 21.1±1.8 years, body mass 83.6±13.1kg, height 1.82±0.1m; mean±s). Each participant performed two sets of seven sprints over 20m using a Latin rectangular design. The times were recorded at 10 and 20m using electronic speed gates. The sprints of 13 players were video-recorded to allow calculation of stride length and frequency. For both sprints, a quadratic relationship was observed between sprint time and resistance as sprint time increased from 2.94s to 3.80s from 0 to 30% resistance. This relationship was statistically significant but considered not to be meaningful for performance because, over the range of resistances used in this study, the quadratic model was never more than 1% (in terms of sprint time) from the linear model. As resistance increased, the stride length shortened, with mean values of 1.63±0.13m at 0% body mass and 1.33±0.13m at 30% of body mass. There was no significant change in stride frequency with increasing resistance. The results show that in general there is an increase in sprint time with an increase in resistance. No particular resistance in the range tested (0-30%) can be recommended for practice.